2023
DOI: 10.1002/edm2.402
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial about effects of prebiotic and probiotic supplementation on weight loss, psychological profile and metabolic parameters in obese subjects

Abstract: Introduction The management of obesity is difficult with many failures of lifestyle measures, hence the need to broaden the range of treatments prescribed. The aim of our work was to study the influence of pre and probiotics on weight loss psychological profile and metabolic parameters in obese patients. Methods It is a clinical trial involving 45 obese patients, recruited from the Obesity Unit of the National Institute of Nutrition between March and August 2022 divided into three groups: diet only (low‐carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…The Firmicutes/Bacteroidetes relationship has often been considered as a possible hallmark of obesity, there is still controversy on this issue due to the relative abundance of the Firmicutes and Bacteroidetes phyla being highly variable among individuals within the same population [80]. This is likely due to many lifestyle factors, including diet, physical activity, food additives and contaminants, antibiotic consumption, physical activity, among others that influence the composition of the microbiota in the gastrointestinal tract [2,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…The Firmicutes/Bacteroidetes relationship has often been considered as a possible hallmark of obesity, there is still controversy on this issue due to the relative abundance of the Firmicutes and Bacteroidetes phyla being highly variable among individuals within the same population [80]. This is likely due to many lifestyle factors, including diet, physical activity, food additives and contaminants, antibiotic consumption, physical activity, among others that influence the composition of the microbiota in the gastrointestinal tract [2,81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Although limitations such as short intervention periods and lack of gut microbiota analysis were noted, the study underscores the potential of probiotic-prebiotic synergy in ameliorating mental health and inflammatory markers in cardiovascular patients. Similarly, Othman et al's research on obese individuals revealed favourable outcomes in weight loss, improved metabolic parameters, and reduced psychiatric disorders when prebiotics and probiotics were combined with lifestyle changes [48]. Despite limitations including small sample sizes and short intervention durations, these findings advocate for the incorporation of prebiotics in therapeutic strategies for anxiety, depression, and associated inflammatory conditions, underscoring the importance of modulating the gut microbiota for holistic well-being.…”
Section: Synbiotics and Prebiotics Synbiotic And Prebiotic Interventi...mentioning
confidence: 93%
“…The studies found that probiotic administration resulted in significant reduction in body weight, depression scores, body fat mass, and waist circumference. In the study by Othmann, significant reductions in depression scores, body weight, and waist circumference were found in the intervention arm (probiotic) and control arm (diet) at the 1-month follow-up, but significant reduction in body fat mass only occurred in the intervention arm ( 65 ). In the study by Sanchez, a decrease in BDI scores was found in the intervention arm between phase 1 and 2, and between phase 2 and baseline, whereas no significant changes were observed in the control arm (placebo).…”
Section: The Role Of Probiotics In Treating Mdd In Obese Patientsmentioning
confidence: 96%